Research Trends of Socio-Scientific Issues (SSI) in Bibliometric Analysis: Implications for Science Education (2010-2023) (Journal of Science Learning, 2026)
Socio-Scientific Issues (SSI) are socially relevant and controversial topics that possess both conceptual and procedural connections to scientific content, making them highly pertinent to science education. Despite their growing integration into instructional practices, comprehensive studies that systematically map publication trends related to SSI in science education remain scarce. This study addresses that gap by conducting a bibliometric analysis of journal articles indexed in the Scopus database from 2010 to 2023, employing VOSviewer for visualization. A total of 174 articles were analyzed using bibliometric mapping techniques. The results indicate a significant rise in publication activity, peaking in 2023, with research predominantly centered on keywords such as socio-scientific issues, science education, scientific literacy, and education for sustainable development, and driven by major contributions from the United States, Germany, and Turkey. These findings highlight the growing global focus on SSI research and the influential role of leading authors such as Troy D. Sadler and Ingo Eilks. This study provides an overview of current research trends and suggests the need for expanded international collaboration and curriculum development to strengthen SSI integration in science education.